(untitled) (Revista Investigación & praxis en CS Sociales, 2024)
This social intervention project investigates the recognition of cultural diversity as a means for social transformation among children in the Vereda Monteadentro, Pamplona, Norte de Santander. It is based on the premise that cultural diversity enriches societies, promotes social cohesion, and reduces existing gaps. The methodology employed is qualitative, grounded in the constructivist paradigm and action research. Techniques such as semi-structured interviews and group workshops were used to collect data from children aged 8 to 12 years, allowing for an exploration of their perceptions regarding cultural diversity and its potential to generate significant social change. The proposal includes a series of musical workshops designed to be both engaging and educational. Through music, children learn about cultural diversity and its transformative capacity. Activities range from teaching musical instruments to creating songs and community integrations that celebrate this diversity. The objective is to educate children on the importance of cultural diversity, fostering greater social cohesion and a sense of shared identity within their community. Expected outcomes include a deeper understanding and renewed respect for cultural differences, contributing to a more just and cohesive society. Ultimately, it emphasizes that cultural diversity holds significant potential for driving social transformation, provided it is implemented with strategies that promote mutual recognition, community engagement, respect, and collaboration.